The impact of azithromycin therapy on the airway microbiota in asthma - Slater, Mariel; Rivett, Damian W.; Williams, Lisa; Martin, Matthew; Harrison, Timothy W.; Sayers, Ian; Bruce, Kenneth D.; Shaw, Dominick E. (BMJ Publishing Group, 2014)
There is interest in the use of macrolide antibiotics in asthma. Macrolides have been shown to improve airway hyperresponsiveness (AHR) and measures of airway inflammation.The degree of AHR may relate to the microbiota present in the airways, with a recent study reporting that patients with asthma with a significant improvement in AHR following treatment with clarithromycin had a higher bacterial diversity prior to treatment. To our knowledge, the impact on the asthmatic airway microbiota of an antibiotic has not been reported and we therefore set out to establish if macrolide therapy was associated with a change in airway microbiota in asthma.